Facile synthesis of chitosan-capped ZnS nanoparticles as a soft biomimetic material in biosensing applications. Issue 7 (July 2016) - Suganthi, G.; Ramanathan, Giriprasath; Arockiadoss, T.; Sivagnanam, Uma Tiruchirapalli
Graphical abstract: Highlights: Biosensors based on cholesterol oxidase (ChoX) using chitosan (CHI)-capped ZnS nanoparticles were fabricated. These nanoparticles were simple and stable with high surface-to-volume ratio. They act as an effective mediator between the enzyme and the electrode. They possess excellent electrochemical and biological properties. They are biocompatible for biosensor applications. Abstract: In this article, we report the novel fabrication of a cholesterol biosensor based on cholesterol oxidase (ChOx) using chitosan (CHI)-capped ZnS nanoparticles (ZnS/CHI). ZnS/CHI was synthesized by an in situ aqueous chemical precipitation of ZnS in the presence of chitosan (CHI). Here, CHI was used to introduce amino groups onto ZnS to improve the catalytic activity. The synthesized ZnS/CHI nanoparticles were characterized using X-ray diffractometry (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS) and Fourier transform infrared (FTIR) techniques. The cholesterol biosensor was fabricated by drop-casting ZnS/CHI over a conductive carbon support followed by the deposition of ChOx over ZnS/CHI and it acts as an active (working) electrode. Further, the performance of the biosensor was investigated by electrochemical method. The response time of biosensor is 5 s, the linearity ranged from 10 to 350 μM of cholesterol with 5 μM as the detection limit and the shelf-life was 10 weeks under refrigerated conditions at 4 °C. ZnS and ZnS/CHI exhibit excellent biocompatibility with fibroblast (NIH 3T3) and human keratinocyte (HaCaT) cells with better cell viability and cell proliferation. These biologically active and sensitive nanocomposites have a potential role in biosensor application.